Taxation, aggregates and the household - Nezih Guner; Remzi Kaygusuz; Gustavo Ventura (Institute for the Study of Labor (IZA), 2008)
We evaluate reforms to the U.S. tax system in a dynamic setup with heterogeneous married and single households, and with an operative extensive margin in labor supply. We restrict our model with observations on gender and skill premia, labor force participation of married females across skill groups, and the structure of marital sorting. We study four revenue-neutral tax reforms: a proportional consumption tax, a proportional income tax, a progressive consumption tax, and a reform in which married individuals file taxes separately. Our findings indicate that tax reforms are accompanied by large and differential effects on labor supply: while hours per-worker display small increases, total hours and female labor force participation increase substantially. Married females account for more than 50% of the changes in hours associated to reforms, and their importance increases sharply for values of the intertemporal labor supply elasticity on the low side of empirical estimates. Tax reforms in a standard version of the model result in output gains that are up to 15% lower than in our benchmark economy.
Keywords: E62; 330; Taxation; two-earner households; labor force participation; Steuerreform; Verbrauchsteuer; Einkommensteuer; Familienbesteuerung; Alleinlebende; Arbeitsangebot; Theorie; USA